Efektivitas Pembelajaran Kitab Al-Af’al Al-Yaumiyyah pada Daurah Ramadhan di Pon Pes Dalwa - Baharun, Segaf; Nur Hanifansyah (Shaut al Arabiyyah, 2024)
This study explores the effectiveness of Kitab Al-Af’al Al-Yaumiyyah in enhancing Arabic vocabulary acquisition and language proficiency among students during the Daurah Ramadhan program at Pondok Pesantren Darullughah Wadda’wah (Dalwa). Employing a qualitative approach, the research focuses on the experiences of students and instructors, identifying challenges and teaching strategies. The study involved 50 students aged 15-18 years, with a research design encompassing pre-intervention, intervention, and post-intervention phases. The teaching methods included daily vocabulary memorization, group discussions, sentence practice, and daily evaluations. The findings reveal that the book significantly aids students in understanding everyday verbs, reinforcing grammar acquisition, and boosting their confidence in speaking. Despite challenges such as the short duration of the program and the heterogeneity of students’ abilities, chunking and mnemonic methods proved effective in facilitating learning. This study offers new insights into the importance of structured materials in intensive learning and is expected to serve as a reference for developing similar programs in other pesantren.